2000
DOI: 10.1159/000016799
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Assessment of Collagen Types I, III, IV and VI in Biopsy Samples of the Bovine Uterine Wall Collected during the Oestrous Cycle

Abstract: Uterine biopsies were collected at cycle days 1 (oestrous), 8, 15 and 19 in six cows. Unfixed cryostat sections were used to immunolocalise collagen types I, III, IV and VI by an indirect FITC method. Collagen I was sparsely found in the endometrium where it formed a fine meshwork of thin fibres directly below the surface epithelium, clearly visible only at cycle days 8 and 15. Collagen III formed the bulk of connective tissue fibres and was arranged in fine aggregates within the superficial endometrial stroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
4
16
0
Order By: Relevance
“…In the present study, the expression of type IV collagen and laminin decreased during the implantation period, and they were reconstructed in the maternal crypts soon after this period. This result agrees with that of Boss [2]. These dramatic events commonly occur in ruminants [9].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the expression of type IV collagen and laminin decreased during the implantation period, and they were reconstructed in the maternal crypts soon after this period. This result agrees with that of Boss [2]. These dramatic events commonly occur in ruminants [9].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, type I collagen was found sparsely in all areas of the endometrium, and its expression was rather intensive below the epithelium on day 14 of the estrous cycle. The expression pattern of type I collagen was confirmed as identical to that of previous reports [2]. Fibronectin binds to a number of biological macromolecules including heparin, types I, II, II and V collagens, the fibrin and integrin family, and regulates many functions of the cell such as growth, differentiation, shape, migration, etc.…”
Section: Discussionsupporting
confidence: 87%
“…At the same time, BNCs expressed PRP-1 and heparanase in limited areas [33,37]. Although BNCs are also a Endometrial remodeling is another crucial factor for the success of implantation and placentation [38]. The importance of the role of MMPs, particularly gelatinases (MMP-2, MMP-9), in ECM degradation and remodeling have been studied in various physiological and pathological states, such as implantation, wound healing and cancer development [39].…”
Section: Role Of Mmps In Endometrial Remodeling Around the Time Of Immentioning
confidence: 99%
“…It is known that interstitial collagen is not homogenous, but it is composed mainly of collagen types I and III. Studies that analyze and quantify the possible functional significance of the degree of heterogeneity of both collagen types in normal or pathological tissue have shown that tissue structure and function are associated with the relative amounts and proportions of ECM proteins, mainly of the collagen, and corroborate the physiological importance of the endometrial stroma and its proteins (Hance & Crystal 1977, Boos 2000. In the present study, we analyzed the effect of the MPA administration on deposit of uterine collagen in the ECM and demonstrated the coexistence of collagen type I and type III in canine uterus.…”
Section: Discussionmentioning
confidence: 91%